Febrile urticaria in a family: uncommon manifestation of a common disease - Sharma, Vishal; Singhal, Mayank; Sharma, Alka; Kumar, Vivek (The Journal of Infection in Developing Countries, 2012)
Cutaneous manifestations are uncommon with malaria. These include urticaria, purpura fulminans, and petechial rash. We report on a series of three patients from a single family who had an urticarial rash with fever that was subsequently diagnosed to be caused by malaria. Urticarial rash has been previously reported with both falciparum and vivax malaria infections. Although the exact pathogenesis is not clear urticarial rash might be related with IgE mediated mast cell degranulation.